Auto indoor hydroponics plant growth chamber - Al-Talib, Ammar A. M.; Tew, Hwa Hui; Sarah ‘Atifah, Saruchi; Noor Idayu, Mohd Tahir; Nor Fazilah, Abdullah (ALife Robotics Corporation Ltd., 2024)
The objective of this project is to build an auto indoor hydroponics plant growing chamber that has an auto monitoring and controlling system. A ESP32 based hydroponics electrical system is built with the attachment of hardware components such as temperature and humidity sensor, light intensity sensor, water level sensor, and water flow rate sensor. The software development of the system is through Arduino IoT Cloud platform, which has an overall suitability in terms of features, cost, and user intuitiveness for starters. Results have shown that ESP32 can ensure stable power supply. After testing and validation, all of the electrical components are stored in a power enclosure box to prevent contact with liquid. In short, the developed auto indoor hydroponics plant growth chamber has effectively demonstrated the ability in easing the plant cultivation procedure for agricultural community.